Determining the stress of rock massif - Zlatanović Dragan; Ljubojev Milenko; Stojanović Zoran; Stojanović Goran (Mining and Metallurgy Engineering Bor, 2014)
Defining the stress rock massif is essential for design of underground facilities and methods of mining in the mines. Assessment the value of stress state of rock massif and rock strength in the various loads allows rational design. This is of particular importance when sizing columns, determining the extent of excavation, the cross-sections of underground rooms in problems with rock bursts and others. This paper briefly gives the basic methods of determining the rock massif stress as part of a study that is aimed to facilitate development of engineering-geological and geomechanical model of the rock massif along the tunnel route under the flotation tailing dump Veliki Krivelj and underground facilities in Jama Bor as the numerical analysis could be applied of the stress-strain state of rocks around the built facilities.